Being a Christian husband : a biblical perspective - Hamer, Colin, 1949- (Darlington, England ; Auburn, Mass. : Evangelical Press, 2005)
Hamer describes the ways that a Christlike husband should take responsibility for the well-being of his wife and family. His arguments are faithful to Scripture and relevant to the modern world. From Adam's experience in Eden, to God's first lessons to him, their outworking in the Old Testament, and then more fully in the teaching of the New Testament, this book deals with what it is to be the husband God intended.
Keywords: Husbands -- Biblical teaching